The Growth of the Industrial City and Inner Toronto's Vanished Church Buildings - Caulfield, Jon (Urban History Review / Revue d'histoire urbaine, 1995)
Based on research about ninety churches located in inner Toronto in 1893, this article considers four explanations for the disappearance or adaption to new uses of many of these buildings and concludes (1) that the city's shift to industrial urbanism, as well as a degree of ecclesiastic overdevelopment, were the main factors leading to church abandonment and (2) that evidence does not strongly support secularization or highest-best-use hypotheses.